MEMBANGUN TOLERANSI BERAGAMA MELALUI PENGEMBANGAN KONSEP DIRI DAN KECERDASAN EMOSI - Komari Komari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2022)
In Indonesia, which has a plural society, the differences in religious doctrines are often potential conflict, the inter-religious tolerance for peaceful coexistence deserve special attention from the various elements of government and society. The purpose of this study is to determine the relationship between self-concept and emotional intelligence with religious tolerance. The subjects in this study are villagers Ringinpitu, District Tanggungharjo, Grobogan, Central Java and have productive age (18-40 years) some 335 people. Methods of data collection using interviews and likert scale. Analysis of the data use is multiple regression analysis. The results of this study indicate that there is a significant relationship concepts of self and emotional intelligence with religious tolerance, as indicated by the value of R2 = 0.566; F= 216.779 (p <0.01), which means major hypothesis proposed is acceptable. The concepts of self and emotional intelligence contribute effectively simultaneously by 56.6%.